Training on Eco-Enzyme Production From Fruit Waste for the Community of Mata Air Village, in Padang Selatan Subdistrict, Padang City - Trisfa Augia; Muhammad Ilham Basgoro; Muhammad Agung Satriya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The waste problem is a challenge for cities, especially in developing countries. Waste management is closely related to population, community values and behavior, and existing organizations and systems. Organic waste refers to waste materials that can decompose naturally and be converted into compost. It includes various types of waste, such as food scraps, dry leaves, and vegetables. Based on the literature obtained, it was reported that the City of Padang produces 600 tons of waste daily and ends up in the Final Disposal Site (TPA) without any follow-up or effective management. A very efficient approach to managing organic waste involves transforming the waste into Eco-enzymes, a remarkable discovery made by Dr. Rasukon Poompanvong from Thailand over three decades ago. This eco-enzyme training was conducted on 16 September 2023 at the Cendana residence in Koto Kaciak, Padang City, West Sumatra-Indonesia. The results of the activities presented by the resource person to the community provided knowledge to the community regarding eco-enzymes. Eco-enzyme training for the community has been carried out. It was concluded that eco-enzyme can be used to reduce waste, especially organic waste, which has many benefits.